"I Need Child Care!": Using Funds of Knowledge, Addressing Challenges, and Developing Literacies With a Classroom Community of Adult ESL Learners. (November 2019) - Cun, Aijuan; McVee, Mary B.; Vasquez, Christopher
Many immigrants and refugees in the United States must confront different linguistic and cultural contexts in their everyday life. As part of a larger ethnographic study related to refugee families and literacy, this qualitative study explores how adult English as a second language (ESL) students help their classmate Htoo Eh find ways to deal with an everyday life challenge. This study utilized two supporting theoretical frameworks: funds of knowledge and literacy as a social practice. Data sources included field notes, transcripts of video recording, artifacts, as well as conservations with the teacher and welfare coordinators. Findings demonstrate that community members utilized two funds of knowledge in particular: social network and life experience to help the focal participant. Findings also showed that adult ESL students assisted their classmates in developing three types of literacies, which were finding and obtaining childcare, knowing how the system works, and communicating with the caseworker in order to deal with an everyday life challenge. These findings suggest that educators should recognize and value adult ESL learners' funds of knowledge as well as incorporate the knowledge into instruction. Educators also should open up space for these learners to develop literacies together as a community.